2011
DOI: 10.2515/therapie/2011042
|View full text |Cite
|
Sign up to set email alerts
|

Les méthodes adaptatives : quand et comment les utiliser dans les essais cliniques ?

Abstract: Texte reçu le 8 avril 2011 ; accepté le 16 mai 2011Mots clés : analyse intermédiaire ; essais adaptatifs ; modification du plan d'expérience ; sélection de traitement Résumé -On définit les schémas adaptatifs pour les essais cliniques comme les schémas qui utilisent les données accumulées dans l'essai pour en modifier éventuellement certains aspects, sans compromettre la validité et l'intégrité de l'essai. Par rapport aux essais plus traditionnels, les schémas adaptatifs permettent en théorie de produire la mê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The review found some key publications that discussed why the reporting of AD trials requires special consideration and reporting suggestions or recommendations for particular types of AD trials [ 23 , 25 , 33 , 34 , 38 , 45 , 51 , 53 61 ]. ADs are not immune to potential biases and limitations despite their appealing nature and promising benefits [ 9 , 50 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…The review found some key publications that discussed why the reporting of AD trials requires special consideration and reporting suggestions or recommendations for particular types of AD trials [ 23 , 25 , 33 , 34 , 38 , 45 , 51 , 53 61 ]. ADs are not immune to potential biases and limitations despite their appealing nature and promising benefits [ 9 , 50 , 53 ].…”
Section: Methodsmentioning
confidence: 99%